PENGARUH PENAMBAHAN KUNYIT PUTIH (Curcuma zedoaria) TERHADAP AKTIVITAS AIR, TOTAL PLATE CONUT (TPC), STAPHYLOCOCCUS AUREUS DAN ESCHERICHIA COLI PADA TELUR ASIN (The influence of addition white tumeric (Curcuma zedoari) on water activity, total plate.... - Ermalinda Kasi; Gemini E.M. Malelak; Heri Armadianto; Gustaf Oematan (Universitas Nusa Cendana, 2022)
Using of Curcuma zedoaria in food processing because of the presence of bioactive compounds such as: phenols, flavonoids and tannins which act as antimicrobials. The purposs of this experiment were to evaluate the effect of adding Curcuma zedoaria on salted egg quality. Completely randomized design (CRD) 5 x 3 was used in this experiment. The treatment used was the addition of white turmeric (Curcuma zedoaria) as much as 0%, 30%, 40%, 50% and 60%. Every treatment consisted of three replications. Analysis of Variance (ANOVA) was used in this experiment followed by Duncan test to test the different among treatment. The results showed that the addition of white turmeric to a level of 60% did not affect the water activity value (aw), causing an increasing in the TPC value, except for 50% (P<0.05), while Staphylococcus aureus and Escherichia coli were detected negative for all samples. The addition of white turmeric as much as 50%, gave the lowest TPC value. In processing salted eggs, it is necessary to ensure the age of the eggs used and storage methods so as to avoid contamination by microbes.